Juridical Analysis Of Credit Agreements With Shopee Paylater - Agustini, Shenti (JUSTISI, 2023)
Technological developments have an impact on today’s business world. Shopee is an online buying and selling application with payment methods made online, namely through the shopee paylater feature or what can be called an online credit agreement. However, there are several cases of default on credit agreements made through the shopee paylater feature. The purpose of this study is to analyze the form and legitimacy of the shopee paylater and settlement of default cases that occur in credit agreements through the shopee paylater. The research method used is normative juridical. The results of the study show that the form of the shopee paylater credit agreement is a standard form of agreement and has legal validity based on the Civil Code. Then the standard agreement is also an implementation of the principle of contractual freedom. If there is a default case in the credit agreement through the shopee paylater, it can be resolved through litigation and non-litigation. Keywords: Credit, Agreement, Shopee